Lipoprotein(a) and inflammation: A dangerous duet leading to endothelial loss of integrity. (May 2017) - Pirro, Matteo; Bianconi, Vanessa; Paciullo, Francesco; Mannarino, Massimo R.; Bagaglia, Francesco; Sahebkar, Amirhossein
Graphical abstract: Lp(a), inflammation and endothelial injury. Abstract: Lipoprotein(a) [Lp(a)] is an enigmatic lipoprotein whose ancestral useful properties have been gradually obscured by its adverse pro-atherogenic and pro-thrombotic effects, that culminate into an increased risk of ischemic cardiovascular events. Although plasma Lp(a) levels are largely determined on a genetic basis, multiple factors have been reported to interfere with its plasma levels. Inflammation is one of these factors and it is believed to promote pro-atherogenic and pro-thrombotic changes leading to increased cardiovascular disease risk. The influence of inflammation on plasma Lp(a) levels is variable, with studies reporting either increased, reduced or unchanged Lp(a) expression and plasma concentrations following exposure to pro-inflammatory stimuli. The complex association between inflammation and Lp(a) is further amplified by additional findings showing that Lp(a) may promote the expression of a plethora of pro-inflammatory cytokines and induces the endothelium to switch into an activated status which results in adhesion molecules expression and inflammatory cells invasion into the arterial wall. In this picture, it emerges that increased plasma Lp(a) levels and inflammation may coexist and their coexistence may exert a deleterious impact on endothelial integrity both at a functional and structural level. Also, the detrimental duet of inflammation and Lp(a) may interfere with the physiological endothelial repair response, thus further amplifying endothelial loss of integrity and protective functions. A fundamental understanding of the interaction between Lp(a) and inflammation is critical for our comprehension of the mechanisms leading to the derangement of endothelial homeostasis and vascular dysfunction.